Composites Prepared from Rice Husk and Recycled/Virgin HDPE with Addition of CouplingAgent - Farid Mulana (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Compositesweremade from recycled HDPE and virgin HDPE as matrix and ricehusk as filler and also added with polyethylene-graft-maleic anhydride (MAPE) as a coupling agent to improve the physical and mechanical properties of composites. Theaim of study is to find the optimum condition of the type of used matrixs and the percentage of added coupling agent on the quality of the producedcomposites. Compositeswere prepared byhot press method. Hot press process was performed at a temperature of 150 oC for 30 minutes.After cooling to room temperature, the product was tested oftensile strength, bending strength, thermal test and FTIR. The results show thatcompositesprepared byvirgin HDPE have much betterphysical and mechanical properties compared to composites prepared by recycled HDPE. The highest tensile strength valueof 5.69 MPawas foundon composite withmatrix of virgin HDPE and addition of 4 wt% MAPE. While the highest bending strength valueof 0.35 Mpa was obtained oncomposite with matrix of recycled HDPE and addition of 2 wt% MAPE. The presence of a number of MAPE concentration in the mixture resulted in increased adhesion properties between rice husk and HDPE thereby increasing the physical mechanical properties of composites.